El género Baldellia Parl. (Alismataceae) en la Península Ibérica, Baleares y Marruecos - Talavera, Salvador; Casimiro-Soriguer, Ramón; Balao, Francisco; Molina Abril, José Antonio; Pizarro, José (Acta Botanica Malacitana, 2008)
The genus Baldellia Parl. (Alismataceae) in the Iberian Peninsula, Balearic Island and Morocco Palabras clave. Baldellia repens, taxones infraespecíficos, W mediterráneo. Key words. Baldellia repens, infraespecific taxa, W mediterranean.